Suppressing Sorbitol Synthesis Substantially Alters the Global Expression Profile of Stress Response Genes in Apple (Malus domestica) Leaves. (15th June 2015) - Wu, Ting; Wang, Yi; Zheng, Yi; Fei, Zhangjun; Dandekar, Abhaya M.; Xu, Kenong; Han, Zhenhai; Cheng, Lailiang
Abstract : Sorbitol is a major product of photosynthesis in apple ( Malus domestica ) that is involved in carbohydrate metabolism and stress tolerance. However, little is known about how the global transcript levels in apple leaves respond to decreased sorbitol synthesis. In this study we used RNA sequencing (RNA-seq) profiling to characterize the transcriptome of leaves from transgenic lines of the apple cultivar 'Greensleeves' exhibiting suppressed expression of aldose-6-phosphate reductase (A6PR) to gain insights into sorbitol function and the consequences of decreased sorbitol synthesis on gene expression. We observed that, although the leaves of the low sorbitol transgenic lines accumulate higher levels of various primary metabolites, only very limited changes were found in the levels of transcripts associated with primary metabolism. We suggest that this is indicative of post-transcriptional and/or post-translational regulation of primary metabolite accumulation and central carbon metabolism. However, we identified significantly enriched gene ontology terms belonging to the 'stress related process' category in the antisense lines ( P -value < 0.05). These include genes involved in the synthesis/degradation of abscisic acid, salicylic acid and jasmonic acid, nucleotide-binding site leucine-rich repeat (NBS-LRR) disease resistance genes and ATP-binding cassette (ABC) transporter genes. This suggests that sorbitol plays a role in the responses of apple trees to abiotic and biotic stresses.